The development experience - Sandford, S. (International Livestock Centre for Africa, 1983)
Discusses pastoral systems research (PSR) within the framework of the experience of livestock and pastoral development in Africa during the last 50 years, analyzing data on livestock population & productivity in relation to the welfare of pastoralists; and examines previous efforts in pastoral development relevant to PSR approach.